Quartz fabric variations across the greenschist facies shear zone separating the Zermatt-Saas and combin ophiolitic zones, Upper Val Gressoney, Western Alps - Savignano, E.; Reddy, Steven; Bridges, J.; Mazzoli, S. (ISTITUTO DI GEOSCIENZE E GEORISORSE CNR, 2016)
The Gressoney Shear Zone (GSZ) consists of a ca. 500 m thick, intensely deformed rock panel located at the top of the high-pressure ophiolitic rocks of the Zermatt-Saas Zone in the Western Alps. This greenschist-facies shear zone accommodated multiple non-coaxial deformation events with contrasting kinematics. In this study, detailed field mapping and structural analysis were integrated with the study of crystallographic preferred orientation (CPO) from mylonites associated with the GSZ. Quartz CPO displays a systematic variation across the shear zone: moving from the basal shear zone boundary, the c-axes pattern changes from type II cross-girdle distribution, to an asymmetric pattern characterized by clustering of c-axes on one side of the Z-direction (inclined single girdle), to a central cluster in the Y-direction. The observed CPO patterns are consistent with increasing shear strain toward the basal contact, which probably controls the transition from broad peripheral maxima indicative of basal slip to an inclined single girdle with no maxima, which is indicative of prism slip, and finally an elongate single maximum at the girdle centre produced by a combination of prism and rhomb slip. Our results further indicate that basal slip is dominant in pure quartz domains, whereas with increasing proportion of second phases, prism <c> slip is activated. These features confirm that CPOs obtained from the almost pure quartzites analysed in most published studies, and generally associated with the activation of distinct slip systems controlled by temperature, cannot be straightforwardly applied to the analysis of heterogeneous shear zones and/or polymineralic mylonites. From a regional point of view, the structures observed in the field and the fabric analyses are consistent with top-to-the-SE extension post-dating subductionrelated high-pressure metamorphism and collisional nappe stacking in the studied sector of the Western Alps.